Diversification of Pakistani Amelogenin-Y-Null Male Haplotypes - Nasir Siddique; Ahmad Ali Shahid; Kalsoom Sughra (Scientifica)
Amelogenin is a common sex typing marker encountered in forensic case work. Phenotypically normal males have been reported in the literature who exhibit anomalous amelogenin allele. These males express only a single amelogenin peak representing AMEL-X and are called as AMEL-Y-null males. Gender misclassification of such individuals is an obvious consequence of this mutation, as a male sample would falsely appear to be a female sample. This study was aimed to attribute the AMEL-Y-null male DNA profiles encountered in forensic casework in the Pakistani population to appropriate phylogenetic clade based on shared ancestry. A total of 18 null AMEL-Y males were screened out of the sample pool of 5000 male individuals, reflecting mutational frequency of 0.36%. A common phylogenetic ancestor is suggested for 17 individuals, based on computational analysis of the Y-STR haplotypes, shown to be belonging to the J haplogroup while only one sample belonged to the R group. The samples in J groups showed homology with subclades J2b2a M241 and J2b2a PH1648, while R group individual showed 100% homology with R1a. Data are reported after haplotype network development of AMEL-Y-null Pakistani males using Network 10.0 for the study of evolutionary distances and emergence of nodes.